Encyclopedia of Environmental Microbiology 2003
DOI: 10.1002/0471263397.env202
|View full text |Cite
|
Sign up to set email alerts
|

Pathogens in Environmental Biofilms

Abstract: Biofilm Structure Autochthonous Biofilm Microflora Autochthonous Biofilm Pathogens Allochthonous Biofilm Pathogens Biofilm Safe Haven

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 125 publications
1
31
0
Order By: Relevance
“…It has also been shown that bacteria attached to surfaces show greater resistance to disinfection (15,19,20,36). Biofilms in distribution systems may provide a favorable condition for some bacteria, such as opportunistic pathogens (e.g., Legionella spp., Pseudomonas aeruginosa, and Mycobacterium avium), to colonize it and may harbor pathogens, such as Salmonella enterica serovar Typhimurium, which have entered the distribution system (1,5,18,28). It has been shown in lab-scale experiments that E. coli can survive in biofilters (24) and even multiply in the biofilm (17,34,40), which again raises the question of its suitability as a drinking water quality indicator.…”
mentioning
confidence: 99%
“…It has also been shown that bacteria attached to surfaces show greater resistance to disinfection (15,19,20,36). Biofilms in distribution systems may provide a favorable condition for some bacteria, such as opportunistic pathogens (e.g., Legionella spp., Pseudomonas aeruginosa, and Mycobacterium avium), to colonize it and may harbor pathogens, such as Salmonella enterica serovar Typhimurium, which have entered the distribution system (1,5,18,28). It has been shown in lab-scale experiments that E. coli can survive in biofilters (24) and even multiply in the biofilm (17,34,40), which again raises the question of its suitability as a drinking water quality indicator.…”
mentioning
confidence: 99%
“…The inclusion and persistence of naturally occurring L. pneumophila at cold-water temperatures and multiplication of these bacteria at warm-water temperatures in biofilms of autochthonous water bacteria have been observed on various plumbing materials including ethylene-propylene, PE-X, non-plasticized PVC and copper (Keevil 2003;Gião et al 2009a, b). Seeding experiments indicated that L. pneumophila could become integrated in pre-existing biofilms and survive or even multiply in these biofilms, depending on the environmental conditions (Armon et al 1997;Långmark et al 2005;Lehtola et al 2007;Benölken et al 2010).…”
Section: Pneumophila and P Aeruginosa Incorporated Into Drinking mentioning
confidence: 99%
“…Certain types of plastic and elastomeric materials can promote biofilm formation due to the release of biodegradable compounds such as monomers or additives like plasticizers, anti-oxidants, providing favorable nutrient conditions for microorganisms (Schoenen and Schoeler 1983;van der Wende et al 1989;Keevil 2003;Anonymous 2007). It has been estimated that about 95% of all microbial cells present in drinking water distribution systems exist as biofilms on pipe surfaces, only 5% occur in the water phase .…”
Section: Biofilms In Drinking Water Systemsmentioning
confidence: 99%
See 2 more Smart Citations